Is a Little Enough? Paucity of Immune Proteins in Serum of Precocial Neonates of a Marine Carnivoran—the Atlantic Grey Seal - McGill, Suzanne; Burchmore, Richard J. S.; Pomeroy, Patrick P.; Kennedy, Malcolm W. (Frontiers in Ecology and Evolution, 2022)
Mammalian mothers usually provide their offspring with large quantities of immunoglobulins (antibodies) for circulation in blood, either trans-placentally before birth, via colostrum briefly thereafter, or, less commonly, from milk. Neonates of true, phocid seals, however, are peculiarly impoverished in serum immunoglobulins, the levels of which slowly increase but do not reach adult levels by the time of weaning. We investigated whether grey seal (Halichoerus grypus) neonates compensate through an elevation or rapid maturation in levels of serum innate immune factors, namely acute phase and complement proteins. Instead, their sera contained remarkably low levels of acute phase proteins (including C-reactive protein, haptoglobin, hemopexin, ceruloplasmin, orosomucoid), compared to their mothers, that barely increased to adult levels by weaning. For complement, there was a strong demarcation between the early activation and amplification cascade components (present at normal adult levels in pups) and the late lytic membrane attack complex and regulatory proteins (consistently at low relative levels). Phocid neonates therefore differ dramatically from land Carnivorans, such as dogs and cats, in early life immune protection. That neonatal phocids survive this apparent vulnerability to infections between birth and weaning prompts questions as to what other mechanisms protect them, and the adaptive value of their seeming vulnerability.